A boy with developmental delay and a maternally inherited deletion in 15q11q13. Issue 5 (May 1996) - King, M; Hardy, C; Asenbauer, B; Kilpatrick, M; Webb, T
Abstract : A boy was referred at 8 weeks of age for failure to thrive. Cytogenetic and molecular studies showed that he had a large proximal deletion of the maternally derived chromosome 15q. He did not have Angelman syndrome, but at 2 years of age was severely globally delayed. He died at 2 1/2 years of age.